Chłop polski w Europie i Ameryce jako studium inkorporacji grup społecznych i budowania wspólnoty narodowej - Goldberg, Chad Alan (Człowiek i Społeczeństwo, 2019)
The Polish Peasant in Europe and America, a sprawling masterpiece co-authored by W.I. Thomas and F. Znaniecki and published in five volumes between 1918 and 1921, is a widely acknowledged classic of interwar sociology. One of its signal contributions, and a key reason for its classic status, is what James Carey, in his book on the Chicago school of sociology, calls the social disorganization paradigm. In the United States, the Chicago school of sociology subsequently applied this paradigm to interpret a variety of urban social problems in the 1920s and early 1930s, and it remains influential in studies of crime and violence in American sociology today. Chad Alan Goldberg, Chłop polski w Europie i Ameryce jako studium inkorporacji grup społecznych i budowania wspólnoty narodowej [The Polish Peasant in Europe and America as a Study of Civil Incorporation and Nation-Building] edited by M. Nowak, „Człowiek i Społeczeństwo” vol. XLVII: „Chłop polski w Europie i Ameryce” po stu latach [Polish peasant in Europe and America after one hundred years], Poznań 2019, pp. 143–159, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271